Resistência à fratura de facetas oclusais ultrafinas confeccionadas em CAD/CAM e cimentadas em esmalte e dentina - Valenzuela, Eneida Beatriz Sanfelice (2020)
The aim of the study was to evaluate, in vitro, the fracture resistance of occlusal veneers, made by CAD/CAM, with IPS e.max CAD material in thicknesses of 0.6 mm and 0.3 mm bonded to enamel and dentin. Fifty human molars were randomly divided into five groups (n=10): G1 – sound teeth (control); G2 – veneer thickness with 0,3 mm bonded to enamel; G3 – veneer thickness with 0,6 mm bonded to enamel; G4 – veneer thickness with 0,3 mm bonded to dentin; G5 – veneer thickness with 0,6 mm bonded to dentin. The venners were adhesively luted to enamel or dentin and stored in distilled water for 24 hours. After storage, the samples were submitted to mechanical cyclic loading (1 million cycles at 200 N load). After that, the fracture resistance test was performed in a universal testing machine with crosshead speed of 1 mm/minute. The fractures were classificate as reparable and irreparable. Accoding to two-way analysis of variance (ANOVA), only veneers thickness factor was significant (p=0,002). According to Tukey test, means followed by diferent letters represent significant diferences (p<0.05): G1 (3204 N)ab; G2 (3144 N)ab ; G3 (2489 N)b ; G4 (3591 N)a; G5 (2770 N)ab. In the control group the failures were irreparable and in the experimental groups there were reparable and irreparable failures. It was concluded that ultrathin occlusal veneers, luted to enamel or dentin, obtained fracture resistance comparable to that of the sound tooth.